The Influence of Digital Marketing, Product Quality, and Consumer Behavior on Purchase Decisions at Point Coffee Cirebon - Muhammad Farhan Maulana; Yono Maulana; Jefry Romdonny (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of digital marketing, product quality, and consumer behavior on purchasing decisions at Point Coffee Cirebon. This study uses a quantitative approach with a survey method involving 150 respondents who are consumers of Point Coffee Cirebon. Data were collected through a questionnaire that measures consumer perceptions of digital marketing, product quality, and behavioral factors that influence their purchasing decisions. Data analysis was carried out using multiple regression methods to test the influence of each independent variable on purchasing decisions. The results of the study indicate that digital marketing, product quality, and consumer behavior significantly influence consumer purchasing decisions at Point Coffee Cirebon. Specifically, effective digital marketing through social media platforms has a major positive impact on purchasing decisions, followed by product quality which is the main factor in attracting consumers. These findings provide important implications for Point Coffee managers in formulating more targeted marketing strategies that are in accordance with consumer preferences. This study is expected to provide insight for coffee entrepreneurs in improving their business performance through the implementation of appropriate digital marketing strategies and improving product quality.